Resistance to Anti-angiogenic Therapies: A Mechanism Depending on the Time of Exposure to the Drugs - Montemagno, Christopher; Pagès, Gilles (Frontiers in Cell and Developmental Biology, 2020)
Angiogenesis, the formation of new blood vessels from preexisting one, represents a critical process for oxygen and nutrient supply to proliferating cells, therefore promoting tumor growth and metastasis. The Vascular Endothelial Growth Factor (VEGF) pathway is one of the key mediators of angiogenesis in cancer. Therefore, several therapies including monoclonal antibodies or tyrosine kinase inhibitors target this axis. Although preclinical studies demonstrated strong antitumor activity, clinical studies were disappointing. Antiangiogenic drugs, used to treat metastatic patients suffering of different types of cancers, prolonged survival to different extents but are not curative. In this review, we focused on different mechanisms involved in resistance to antiangiogenic therapies from early stage resistance involving mainly tumor cells to late stages related to the adaptation of the microenvironment.